Long-range lateral correlation between self-assembled domains of fluorocarbon-hydrocarbon tetrablocks by quantitative GISAXS - Abuillan, Wasim; Veschgini, Mariam; Mielke, Salomé; Tanaka, Motomu (ChemPhysChem, 2019)
The structure and lateral correlation of fluorocarbon-hydrocarbon tetrablock di(F10Hm) domains at the air/water interface have been determined by quantitative analysis of grazing incidence small-angle X-ray scattering (GISAXS) data. The measured GISAXS signals can be well represented by the full calculation of the form and structure factors. The form factor suggests that di(F10Hm) domains take a hemiellipsoid shape. Both major and minor axes of the hemiellipsoids monotonically increased in response to the elongation of the hydrocarbon blocks, which can be explained by the concominant increase in van der Waals interaction. The structure factor calculated from the GISAXS signals suggests that the domains take an orthorhombic lattice. Remarkably, the lateral correlation can reach over a distance that is more than 14 times longer than the distance to the nearest neighbors. Our data suggest that quantitative GISAXS enables the optimal design of mesoscopic self-assemblies at the air/water interface by fine-tuning of the structures of molecular building blocks.